ISSUES OF CONSIDERATION BY ADMINISTRATIVE COURTS OF APPLICATIONS (COMPLAINTS) AGAINST ADMINISTRATIVE ACTS OF ADMINISTRATIVE BODIES AND ACTIONS (INACTION) OF THEIR OFFICIALS - Rakhmonov Zafarjon Zayniddinovich (Western European Studies, 2025)
This article analyzes the theoretical and practical aspects of consideration by administrative courts of applications and complaints filed against administrative acts adopted by administrative bodies, as well as against actions (inaction) of their officials. The author раскрывает the legal nature of the concept of an administrative act, identifies its distinguishing features from other legal documents, and substantiates the importance of determining an administrative act for establishing judicial jurisdiction. In addition, based on national legislation and judicial practice, the article examines written, oral, electronic, and signal-based forms of administrative acts, as well as the concept of actions and inaction of officials. The study substantiates, from both theoretical and practical perspectives, that the presence or absence of an administrative act is a decisive factor for initiating proceedings in administrative courts
Keywords: Administrative court; administrative act; administrative document